The relationship between maxillary sinus volume and different cephalometric characteristics in orthodontics - Hamad Alqahtani; Sara Basuhail; Fahad Alsulaimani; Khalid H Zawawi; Mohammed Barayan; Ghassan Al Turki; Mona Aly Abbassy (Wolters Kluwer Medknow Publications, 2023)
Introduction: This study aimed to evaluate the maxillary sinus volume (MSV) in both genders in a Saudi sample and among different skeletal patterns. Materials and Methods: This retrospective cross-sectional study included 52 cone-beam computed tomography (CBCT) scans of 18 years or older individuals with complete dentition and healthy medical history. MSV was measured as the mean value of both sides in cubic millimeters (mm3) using OnDemand three-dimensional™ Dental. Cephalometric tracings were conducted on cephalograms obtained from CBCT scans. The beta, A × B, and Frankfort-mandibular plane angles were selected to determine the sagittal and vertical skeletal patterns of the study subjects. Descriptive statistics and other tests were conducted. The significance level was set at P < 0.05. Results: Fifty-two CBCT scans were included in this study (23 males and 29 females), with a mean age of 36 (±14) years. The mean MSV was 14887 (±5030.79) mm3. Males had statistically significantly larger MSV (16517 ± 5335 mm3) compared with females (13595 ± 4,452 mm3) (P = 0.036). There was no statistically significant difference in MSV among all other cephalometric measurements (P > 0.05). Conclusions: The MSV in the studied Saudi sample was larger among males. However, different skeletal patterns have no statistically significant differences in MSV.